Economic evaluation of a dietary intervention for adults with major depression (the "SMILES" trial) - Mary Lou Chatterton; Cathrine Mihalopoulos; Adrienne O'Neil; Catherine Itsiopoulos; Rachelle Opie; David Castle; Sarah Dash; Laima Brazionis; Michael Berk; Felice Jacka (BMC, 2018)
Abstract Background Recently, the efficacy of dietary improvement as a therapeutic intervention for moderate to severe depression was evaluated in a randomised controlled trial. The SMILES trial demonstrated a significant improvement in Montgomery-Åsberg Depression Rating Scale scores favouring the dietary support group compared with a control group over 12 weeks. We used data collected within the trial to evaluate the cost-effectiveness of this novel intervention. Methods In this prospective economic evaluation, sixty-seven adults meeting DSM-IV criteria for a major depressive episode and reporting poor dietary quality were randomised to either seven sessions with a dietitian for dietary support or to an intensity matched social support (befriending) control condition. The primary outcome was Quality Adjusted Life Years (QALYs) as measured by the AQoL-8D, completed at baseline and 12 week follow-up (endpoint) assessment. Costs were evaluated from health sector and societal perspectives. The time required for intervention delivery was costed using hourly wage rates applied to the time in counselling sessions. Food and travel costs were also included in the societal perspective. Data on medications, medical services, workplace absenteeism and presenteesim (paid and unpaid) were collected from study participants using a resource-use questionnaire. Standard Australian unit costs for 2013/2014 were applied. Incremental cost-effectiveness ratios (ICERs) were calculated as the difference in average costs between groups divided by the difference in average QALYs. Confidence intervals were calculated using a non-parametric bootstrap procedure. Results Compared with the social support condition, average total health sector costs were $856 lower (95% CI -1247 to − 160) and average societal costs were $2591 lower (95% CI -3591 to − 198) for those receiving dietary support. These differences were driven by lower costs arising from fewer allied and other health professional visits and lower costs of unpaid productivity. Significant differences in mean QALYs were not found between groups. However, 68 and 69% of bootstrap iterations showed the dietary support intervention was dominant (additional QALYs at less cost) from the health sector and societal perspectives. Conclusions This novel dietary support intervention was found to be likely cost-effective as an adjunctive treatment for depression from both health sector and societal perspectives. Trial registration Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12612000251820. Registered on 29 February 2012.